ISLAM DAN FILOSOFI MASYARAKAT FAKFAK - Mohamadon D.Husen (Wahana Islamika: Jurnal Studi Keislaman, 2018)
Fakfak community is known as religious society, friendly, good manners, maintaining tolerance among religious people, appreciating unity and unity because everything is contained in the philosophy and outlook of life. Philosophy of society Fakfak is a life view that was excavated and formed based on mutual consensus that contains the noble values ​​of the people of Fakfak itself since time immemorial which then used as a bond and then the philosophy or life view is used as a guide and even motivation in running various aspects people's lives. The philosophy contains a substance where all attitudes and worldviews are based on "family religion" or "custom, religion and government" which are summed up into “satu tungku tiga batu”. Thus when the occurrence of Islamic transformation in the land of Papua and in Fakfak in particular it does not necessarily replace the existing values ​​of Islam in the life of the people of Fakfak, even some aspects of the philosophy of society Fakfak is in line with the spirit of Islamic teachings as a religion that brings present "Grace" for nature and its contents including for the people of Fakfak.